Efeitos de manipulações de propriedades formais de estímulos verbais sobre o comportamento - BRAGA, Mariella Vasconcelos Nogueira (2011)
Aiming to investigate the effects of antecedent verbal stimuli on behavior, twenty-four students were exposed to a match to sample procedure. The task consisted of pointing out to each of three comparison stimuli. The correct behavior was reinforced in fixed ratio 6. In Condition 1, the order of the presentation of the stimuli at the beginning of phases 2, 3, 4 and 5 was: corresponding instruction, minimal instruction, corresponding question, minimal question, respectively. The eight conditions differed only in the order in which the verbal stimuli were presented. The corresponding stimuli and corresponding question established the correct behavior in 95% and 33% of the cases, respectively. The minimal stimuli didn't establish the correct behavior. The results have implications on the defining of rules.